Financial analysis of pre and post - merger of HDFC Bank with CBoP - Sanjay, Kumar Bahl; Ramandeep, Гаутам; Санджай, Кумар Бал; Рамандип, Гаутам (Харківський національний автомобільно-дорожній університет, 2017)
In today’s competitive world Mergers and Acquisition is one of the important corporate level strategies. There are various reasons like creating synergy, achieve economies of scale, expand operations and cut costs etc. due to which the entities adopt this strategy. The purpose of our research paper is to go behind the scene highlighting those forces which are playing active role in the mergers and acquisition of Centurion Bank of Punjab and Housing Development Finance Corporation Bank in year 2008. This paper discusses two time slots, one pre and second post-merger period. In these time slots five years before and after merger has been studied by doing financial analysis of the two banks on the basis of following Ratios like, debt equity ratio, financial coverage ratio, net profit margin ratio, return on net worth ratio, credit to deposit ratio etc. The data pre and post-merger was collected and its impact on financial position of HDFC Bank was studied by applying Time Dummy model through SPSS software to test the statistical significance which helps to know that Merger had a positive effect on financial health of the Bank. The results found suggest that the bank has gained efficiency and is able to pass benefits to all stakeholders in the society. Thus it can be said that the banks benefitted from this venture.
Фінансовий аналіз до та після операції поглинання банку «Centurion Bank of Punjab» банком «Housing Development Finance Corporation»
Keywords: Mergers & Acquisition; Banking Industry; Statistical Significance; Time Dummy Model; SPSS; злиття та поглинання; банківський сектор; статистична значимість; Time Dummy Model; SPSS